Implementation of Environmental Care Character Education in Children Aged 5-6 Years - Sidiq, Adelia Miranti; Istiani, Meity; Kustini, Ninik (JOYCED: Journal of Early Childhood Education, 2023)
Providing education is a process of acculturating and empowering students that lasts throughout life. In this process, the role of educators is needed who is able and willing to be a role model, build abilities, and develop students' potential and creativity. The type of research used is a descriptive method with a qualitative approach. This research aims to provide an overview of the Implementation of Character Development. Based on the results of research on the implementation of environmentally caring character education at Bakti IV Bubutan Islamic Kindergarten, Surabaya, the process of implementing environmentally caring character education was carried out by integrating environmentally caring character education into learning activities. This is indicated by the curriculum content used at the Bakti IV Bubutan Islamic Kindergarten, Surabaya, which refers to candy. And the scientific approach in the Merdeka 2020 PAUD Curriculum learning tools for character education already contains character values, starting from CP (learning outcomes), TP (learning objectives) in addition to the semester program and weekly activity plans which already contain character values.  Based on the results of the analysis and discussion, the author can draw conclusions regarding the process of developing environmentally caring character in children through the habituation method used by teachers at the Bakti IV Bubutan Islamic Kindergarten, Surabaya.